The Effect of Five-Finger Relaxation Technique on Anxiety and Stress in Non-Hemorrhagic Stroke Patients at the Inpatient Installation of RSUD Cimacan Cianjur District - Dewi, Rosliana; Fatmala, Syiva Dwi; Yulianti, Maria; Arsyi, Dila Nurul (STIKep PPNI Jawa Barat, 2024)
Aims: The purpose of this study was to examine the effect of five-finger relaxation technique on anxiety and stress in hemorrhagic stroke patients at Cimacan Hospital. Methods: This study used quasi-experiment with nonequivalent control group design. Sample collection using purposive sampling. The sample was 40 people and divided into two groups with 20 people each for the intervention group and control group. Data analysis using Paired Sample T-Test and Independent Sample T-Test. Results: The results showed that after the five-finger relaxation technique was performed on the intervention group, there was a decrease in anxiety levels (p = 0.000) and stress (p = 0.000) in stroke patients, while in the control group there was a decrease in anxiety (p = 0.000) and stress (p = 0.000), and there was a difference between anxiety levels (p = 0.000) and stress (p = 0.000) in the intervention and control groups. Conclusion: There is an effect of five-finger relaxation technique on anxiety and stress in non-hemorrhagic stroke patients, and there are differences in anxiety and stress in the control and intervention groups. It is hoped that this five-finger relaxation technique can be used as an evidence base nursing on non-pharmacological treatment as a form of independent nursing intervention by a nurse in providing nursing care to help in the process of reducing anxiety and stress in stroke patients.